2016
DOI: 10.1371/journal.pone.0160415
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation of 25 Y-Chromosomal and 15 Autosomal STR Loci in the Han Chinese Population of Liaoning Province, Northeast China

Abstract: In the present study, we investigated the genetic characteristics of 25 Y-chromosomal and 15 autosomal short tandem repeat (STR) loci in 305 unrelated Han Chinese male individuals from Liaoning Province using AmpFISTR® Yfiler® Plus and IdentifilerTM PCR amplification kits. Population comparison was performed between Liaoning Han population and different ethnic groups to better understand the genetic background of the Liaoning Han population. For Y-STR loci, the overall haplotype diversity was 0.9997 and the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Principal components analysis was performed with MVSP 3.1 ( http://www.kovcomp.com ) based on allelic frequencies of the 15 autosomal STR loci. Nei’s standard genetic distances between currently studied and previously published populations (Russian 20 , Saraki Pakistan 21 , Korean 22 , Punjabi 23 , Indian 24 , Morocco 25 , Eastern Turkey 26 , Hong Kong 27 , Japanese 28 , Interior Sindh (unpublished), Hungarian 29 , South Iran 30 , Azerbaijan 31 , Turkish Cypriot 32 , Afghanistan 33 , Bangladesh 34 , Malaysia 35 , Kadazan Malaysia 36 , Sindh Pakistan 37 , Iraq 38 , Pashtuns Afghanistan 39 , Tajik Afghanistan 39 , Uzbek Afghanistan 39 , Turkmen Afghanistan 39 , Mongols of Mongolia 40 , Hazara Afghanistan 39 , Kuala Lumpur Malaysia 41 , Miao 42 , East Mongolia of China 43 , Dong 44 , Bouyei 45 , Han Liaoning 46 , Manchu Liaoning 47 , Hui Qinghai 48 , Uyghur China 49 , Russian in China 50 , Dongxiang Qinghai 51 , Salar Qinghai 51 , Kazakh China 13 ) were generated using the Phylip 3.69 package 52 and visualized with Mega7 software 53 .…”
Section: Methodsmentioning
confidence: 99%
“…Principal components analysis was performed with MVSP 3.1 ( http://www.kovcomp.com ) based on allelic frequencies of the 15 autosomal STR loci. Nei’s standard genetic distances between currently studied and previously published populations (Russian 20 , Saraki Pakistan 21 , Korean 22 , Punjabi 23 , Indian 24 , Morocco 25 , Eastern Turkey 26 , Hong Kong 27 , Japanese 28 , Interior Sindh (unpublished), Hungarian 29 , South Iran 30 , Azerbaijan 31 , Turkish Cypriot 32 , Afghanistan 33 , Bangladesh 34 , Malaysia 35 , Kadazan Malaysia 36 , Sindh Pakistan 37 , Iraq 38 , Pashtuns Afghanistan 39 , Tajik Afghanistan 39 , Uzbek Afghanistan 39 , Turkmen Afghanistan 39 , Mongols of Mongolia 40 , Hazara Afghanistan 39 , Kuala Lumpur Malaysia 41 , Miao 42 , East Mongolia of China 43 , Dong 44 , Bouyei 45 , Han Liaoning 46 , Manchu Liaoning 47 , Hui Qinghai 48 , Uyghur China 49 , Russian in China 50 , Dongxiang Qinghai 51 , Salar Qinghai 51 , Kazakh China 13 ) were generated using the Phylip 3.69 package 52 and visualized with Mega7 software 53 .…”
Section: Methodsmentioning
confidence: 99%
“…Using KIR as the panel of genetic marker, the results showed that Eastern Han from Jiangsu province had the closest relationship with Jilin Han, followed by Shanghai Han, indicating that Eastern Han shared a common ancestry, which was consistent to the findings based on other genetic markers, such as autosomal STRs and Y-STRs by Yao et al . 57 . The notable association of Eastern Han with Jilin Han was confirmed by the famous large-scale migration literally called “Crashing into Guandong”.…”
Section: Resultsmentioning
confidence: 99%
“…Liaoning province is located in the northeast of China, with a population of approximately 43 million people. 39 Currently, the incidence rate of MD is <1 case per 100,000 population, with the majority of cases recorded during the springtime, and in the cities of Shenyang and Dalian, from 2004 to 2016. MD mainly affects individuals aged 0-15 years, while children, students and farmers (defined as laborers that travel from rural areas into cities for work) are the three main groups affected.…”
Section: Liaoning Provincementioning
confidence: 99%